A framework for creating standardized outcome measures for patient registries. (September 2014) - Gliklich, Richard E; Leavy, Michelle B; Karl, Jannette; Campion, Daniel M; Levy, Daniel; Berliner, Elise
Aim: Our objectives were to create a conceptual framework for development of standard outcome measures and to design and pilot test a tool for displaying outcome measures.Materials & methods: Information on outcome measures used in registries was gathered through stakeholder discussions, which informed the development of the outcome measurement framework and the related tool.Results: The outcome measurement framework is a conceptual model for how information relevant to evaluating patient outcomes may be defined and collected in a standard way for a broad range of health areas. The related tool facilitates collecting, displaying and searching for information on outcome measures.Conclusion: The model developed through this process offers a framework that can be used to define outcome measures in a standard way across medical conditions.